A New Class of Meromorphic Multivalent Functions Involving an Extended Linear Derivative Operator of Ruscheweyh - Jitendra Awasthi (International Journal of Mathematics And its Applications, 2018)
In this paper,we introduce and discuss a new subclass $A_{p}(λ ,α )$ of meromorphic multivalent functions in the punctured unit disk $U^{* }=\{z:z$ $ε $ $C,0<\left\vert z\right\vert <1\}$ defined by a certain extended linear derivative operator of Ruscheweyh. Coefficients inequality,distortion theorems,closure theorem for this class are obtained.We also obtain radius of starlikeness and radius of convexity for this class.